2020
DOI: 10.1038/s41598-020-67343-5
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of carbon and nitrogen accumulation and translocation of winter wheat plant to improve grain yield and processing quality

Abstract: the objective of this work was to characterize the accumulation of carbon (c) and nitrogen (n), and the translocation of wheat (Triticum aestivum L.) cultivars to achieve both high-quality and highyield. Twenty-four wheat cultivars, including 12 cultivars containing high-quality gluten subunit 5 + 10 at Glu-D1, and 12 cultivars with no Glu-D1 5 + 10, were planted at Yuanyang and Xuchang in Henan Province, during 2016-2017, and 2017-2018 cropping seasons. Wheat cultivars containing Glu-D1 5 + 10 had an advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Subsequently, by using natural population, Huang et al. (2020) found that, at the Glu‐D1 locus, the lines that had 5+10 accumulated more GPC compared with the lines without 5+10, while no significant difference in GPC between NILs 5+10 and 2+12 was found by X. Wang et al. (2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, by using natural population, Huang et al. (2020) found that, at the Glu‐D1 locus, the lines that had 5+10 accumulated more GPC compared with the lines without 5+10, while no significant difference in GPC between NILs 5+10 and 2+12 was found by X. Wang et al. (2018).…”
Section: Resultsmentioning
confidence: 99%
“…Plessis et al (2013) suggested that HMW-GSs composition at the Glu-D1 locus affected GPC by using the method of genome-wide association, but this conclusion was not supported by the study of Würschum et al (2016). Subsequently, by using natural population, Huang et al (2020) found that, at the Glu-D1 locus, the lines that had 5+10 accumulated more GPC compared with the lines without 5+10, while no significant difference in GPC between NILs 5+10 and 2+12 was found by X. Wang et al (2018).…”
Section: Grain Protein Contentmentioning
confidence: 99%
“…Mustang was more tolerant to Cd than was Lancer which can be seen from the IC 50 inhibitory concentration since Mustang exhibited high macro-and micro-nutrients as well photosynthesis pigmentation and MDA content in leaves compared with Lancer. Varietal Cd tolerance levels impair the morphophysiological parameters of different wheat cultivars, such as Pingan 8 (3), Aikang58 (1.98 ± 0.22), Yangmai 20 (2.20), Zhoumai-32 (0.421 ± 0.026), Sceptre (0.105) mg kg −1 soil Cd (Grant and Bailey, 1998;Ci et al, 2010;Arshad et al, 2016;Guo et al, 2019;Zhang et al, 2019;Huang et al, 2020). Furthermore, it was shown that macro-and micro-nutrients in grain uptake by varietal composition was compromised by Cd toxicity, perhaps due to chelating activities inside plants and rhizosphere (Halim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the supply of assimilate to grain originates from the remobilization of assimilates that have been stored in the vegetative plant parts temporarily, as well as from the current assimilation that is transferred directly to the kernel (Santiveri et al., 2004). The grain dry matter of wheat during the grain filling period is mainly supported by the vegetative organs, wherein it strongly influences the grain yield formation (Huang et al., 2020). The estimated proportion contributed from remobilization of pre‐anthesis dry matter to grain yield of wheat ranged between 7% and 57% (Ehdaie & Waines, 2001).…”
Section: Introductionmentioning
confidence: 99%